2018
DOI: 10.1016/j.enbuild.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A framework for monitoring-based commissioning: Identifying variables that act as barriers and enablers to the process

Abstract: The practice of monitoring-based commissioning (MBCx) using energy management and information systems (EMIS) has been shown to enable and help sustain up to 20% energy savings in buildings. Despite research that has quantified the costs, benefits, and energy savings of MBCx, the process remains underutilized. To understand why MBCx is not more frequently adopted and how to encourage its use, this research synthesizes qualitative data from over 40 organizations, currently engaging in MBCx. The outcome of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…There was evidence of cognitive bias in 30% of the elements. For a summary of the barriers without cognitive biases, see Harris et al (2018). In the next section, examples of practical solutions to overcome these biases are suggested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was evidence of cognitive bias in 30% of the elements. For a summary of the barriers without cognitive biases, see Harris et al (2018). In the next section, examples of practical solutions to overcome these biases are suggested.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research describes some commonly experienced technical barriers faced by organizations during the monitoring-based commissioning (MBCx) process such as data configuration and quality. In a study of over 40 organizations using MBCx, Harris et al (2018) found data configuration to be the top barrier. Organizations frequently experienced issues integrating data from hardware, such as submeters, into energy management and information systems (EMIS) due to things like legacy building automation systems (BAS) or information technology (IT) issues such as data security.…”
Section: Background and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…43 Although many efforts to improve metadata by developing semantic models 44,45 are ongoing, the engineering costs for improving metadata for data analytics are still high; this is recognized as the main barrier for implementing smart building solutions in existing buildings. 31,46 Methods to improve quality of metadata. Improving metadata requires, first and foremost, identifying the sources of data.…”
Section: Metadatamentioning
confidence: 99%